Respuesta :

gmany

[tex]4\dfrac{1}{2}\cdot6=\dfrac{4\cdot2+1}{2}\cdot6=\dfrac{9}{\not2_1}\cdot\not6^3=9\cdot3=27[/tex]

Other method:

[tex]4\dfrac{1}{2}\cdot6=\left(4+\dfrac{1}{2}\right)\cdot6\\\\\text{use distributive property}\\\\=(4)(6)+\left(\dfrac{1}{2}\right)(6)=24+3=27[/tex]

ASIAX

Hi there!

To solve a fractional equation such as this you need to turn both factors into fractions. Here is how to sole it:

1) Turn 4 [tex]\frac{1}{2}[/tex] into an improper fraction by taking the 4 and multiplying it by the 2 in the denominator and putting the result in the numerator plus the 1 that is already there.

4×2 = 8

8+1 = 9

Now makes [tex]\frac{9}{2}[/tex]

2) Now make 6 a fraction by putting it over 1, like so:

[tex]\frac{6}{1}[/tex]

3) Now multiply the numerators together first, then multiply the denominators together, like so:

[tex]\frac{9*6}{2*1}[/tex] = [tex]\frac{54}{2}[/tex]

4) Now simplify by dividing 54 by 2 to get the final result:

54÷2 = 27

Your friend, ASIAX

ACCESS MORE